2010
DOI: 10.4103/0970-2113.63606
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and clinical profile of Community acquired pneumonia in hospitalized patients

Abstract: The aim of our study was to obtain comprehensive insight into the bacteriological and clinical profile of community-acquired pneumonia requiring hospitalization. The patient population consisted of 100 patients admitted with the diagnosis of community-acquired pneumonia (CAP), as defined by British Thoracic society, from December 1998 to Dec 2000, at the Sher- i-Kashmir institute of Medical Sciences Soura, Srinagar, India. Gram negative organisms were the commonest cause (19/29), followed by gram positive (10/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 14 publications
7
49
2
Order By: Relevance
“…This is similar to previous published data from our hospital in 2013 13 and also similar to India where the most common isolated organisms reported were Pseudomonas aeruginosa and Staphylococcus aureus. 20 The incidence of Streptococcus pneumoniae is slightly lower in our population compared to western world where it was associated with significant mortality. 8,21 Viruses are also commonly isolated in CAP.…”
Section: Discussionmentioning
confidence: 74%
“…This is similar to previous published data from our hospital in 2013 13 and also similar to India where the most common isolated organisms reported were Pseudomonas aeruginosa and Staphylococcus aureus. 20 The incidence of Streptococcus pneumoniae is slightly lower in our population compared to western world where it was associated with significant mortality. 8,21 Viruses are also commonly isolated in CAP.…”
Section: Discussionmentioning
confidence: 74%
“…Another study in Russia found Staphylococcal aureus and Pseudomonas aeruginosa to be important etiological agents in SCAP [19]. On the contrary in the Asian continent, the most common organisms isolated in patients from India were Pseudomonas aeruginosa (35%) and Staphylococcus aureus (24%) [20]. A relatively higher prevalence of Pseudomonas aeruginosa and Staphylococcus aureus has also been reported in Japan and China [21-24] indicating microbiological spectrum specific to certain epidemiological areas.…”
Section: Discussionmentioning
confidence: 99%
“…[9] The IDSA has adopted the new antipneumococcal fluoroquinolones, namely levofloxacin, sparfloxacin, moxifloxacin and gatifloxacin, as preferred agents for the treatment of both ambulatory and hospitalized patients with CAP and for penicillin-resistant pneumococcal pneumonia. [10] For empiric treatment of the moderately ill-hospitalized patient, the IDSA recommends an extended-spectrum cephalosporin (cefotaxime, ceftriaxone) plus a macrolide or monotherapy with a fluoroquinolone.…”
Section: Discussionmentioning
confidence: 99%